2020
DOI: 10.1016/j.ijrmhm.2019.105088
|View full text |Cite
|
Sign up to set email alerts
|

Carbide grain growth in cemented carbides sintered with alternative binders

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The choice of transition metal such as Co, Fe or Ni, has been done based on their good wettability and solubility of W and C and based on their good mechanical properties. Cermets, also known as Hardmetals are extensively utilized for manufacturing of cutting tools and are classically manufactured by powder sintering [10][11][12][13][14]. Considering several studies, it can be concluded that L-PBF manufacturing of WC-Co parts remains challenging [15][16][17].…”
Section: Additive Manufacturing Of Cermet Produced By Laser Powder Be...mentioning
confidence: 99%
“…The choice of transition metal such as Co, Fe or Ni, has been done based on their good wettability and solubility of W and C and based on their good mechanical properties. Cermets, also known as Hardmetals are extensively utilized for manufacturing of cutting tools and are classically manufactured by powder sintering [10][11][12][13][14]. Considering several studies, it can be concluded that L-PBF manufacturing of WC-Co parts remains challenging [15][16][17].…”
Section: Additive Manufacturing Of Cermet Produced By Laser Powder Be...mentioning
confidence: 99%
“…2f). They are related to the grain growth process in W-rich alloys: nucleation of new layers would be more rapid than lateral growth of these layers, especially in WC-Fe,W [19]. and (0,0,0,1) basal (B) facets.…”
Section: General Features Of Wc Grainsmentioning
confidence: 99%
“…Suitable compositions have to be carefully examined to avoid the formation of detrimental phases [16,17]. Up to now, there has been little research on the exact effect of Ni-or Fe-rich binder on sintering and microstructure evolution [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O metal duro tem sido usado como ferramentas de corte, na usinagem, desde a década de 1920. Conhecido como um material cerâmico, é processado pela rota convencional da metalurgia do pó, sendo fabricado a partir de pós-metálicos, carbonetos de tungstênio (WC) e cobalto (Co), podendo ser utilizado novos ligantes alternativos, especialmente o níquel (Ni) ou ferro (Fe), a combinação de dureza e ductilidade fornece propriedades mecânicas superiores a outras ligas [1]. Em 1933, foi desenvolvido uma liga WC-Ni com a marca RENIK, como substituto da liga WC-Co, pela empresa Moscow Plant of Rare Chemical Elements, para munições e armamentos durante a 2 ª Guerra Mundial [2].…”
Section: Introductionunclassified